DIMENSI SUFISTIK DALAM ISLAM: STUDI ATAS PEMIKIRAN TASAWUF IBN SI>NA> DAN RELEVANSINYA DENGAN DUNIA PENDIDIKAN - Hambali, Yoyo; Supriyanto, Agus; Sabeni, M. (Turats, 2015)
The purpose of this paper is to answer the problem, namely, how the mystical dimension in Islam and how the mystical thought of Ibn Sina and its relevance to the world of Islamic education? The approach used in this paper, among others, the historical approach, hermeneutic, and phenomenological. Discussion of this paper is descriptive-analytic. The conclusion of this paper include that mysticism or Sufism has strong roots of the sources of Islam (Qur'an and Sunnah) and a little more receptive to the influence of outside Islam, especially from Greek philosophy and spiritual traditions of Persia. Ibn Sina as shown in the lives, works and thoughts have a tendency of Sufism. Thoughts on knowledge 'Irfani, mystical love, spirituality, prayer, and ascetic, indicating that spirituality of Ibn Sina not only be at a theoretical level, but also practical. Mystical Dimensions of Ibn Sina can be a thirst quencher in the midst of spiritual aridity due to materialism and pragmatism that swept people today